Incidence and risk factors for clinical omphalitis among neonates in Eastern Uganda using chlorhexidine gel for cord care: a community-cohort study - John Wogabaga; Kathy Burgoine; Abel Kakuru; Brendah Nambozo; Martin Chebet; Josephine Tumuhamye; Benon Wanume; Faith Oguttu; Milton W. Musaba; Agnes Napyo; Solomon Wani; Peter Olupot-Olupot; et al. (BMC Pediatrics)
Abstract Background Omphalitis is a bacterial infection of the umbilicus and/or surrounding tissues, occurring primarily in the neonatal period. Whereas it is known to be a major route of localized and often systemic infection, studies describing incidence and risk factors remain scanty, especially in resource limited settings where the condition is thought to be common. We assessed the incidence and risk factors for omphalitis among neonates born to women who received a birth kit containing chlorhexidine for umbilical cord care after birth in Eastern Uganda. Trial registration for the parent study The BabyGel trial was registered in the Pan African Clinical Trial Registry -(PACTR202004705649428 Registered 1 April 2020, https://pactr.samrc.ac.za/ ). Methods We conducted a community-based cohort study between January 2021 and June 2023. This study was nested within the BabyGel trial. Our outcome of interest was clinical omphalitis, defined as purulent discharge from the umbilical cord stump within the first twenty-eight days of life as witnessed by a study midwife. Data were analyzed using Stata version 17.0. Bivariable and multivariable analyses were conducted using Cox proportional hazard regression models to estimate hazard ratios (HR) of selected exposures and time to omphalitis. Results A total of 2052 neonates were enrolled; half of which were female (51.1%). The incidence of omphalitis was 3.0% (62/2052; 95% confidence interval (CI): 1.9%, 4.4%). The incidence rate of omphalitis was 1.6 cases per 1000 person days (95% CI: 1.1, 2.3). Neonates born at home were twice as likely to develop omphalitis as those born in a health facility (adjusted hazards ratio (AHR) 1.99; 95% CI: 1.01, 3.9). Conclusion The incidence of omphalitis among neonates in Eastern Uganda was low. Home births carried twice the risk for omphalitis. Use of chlorhexidine coupled with close follow-up of neonates in the community by health workers and community health workers might have reduced the risk of omphalitis.